Tumor Screening in Beckwith-Wiedemann Syndrome – To Screen or Not to Screen? - Kalish, Jennifer M. (Am J Med Genet A, 2016)
Beckwith-Wiedemann syndrome (BWS) is the most common imprinting disorder and consequently, one of the most common cancer predisposition disorders. Over the past 20 years, our understanding of the genetics and epigenetics leading to BWS has evolved and genotype/phenotype correlations have become readily apparent. Clinical management of these patients is focused on omphaloceles, hypoglycemia, macroglossia, hemihypertrophy, and tumor screening. Until recently, the need for tumor screening has been thought to be largely uniform across all genetic and epigenetic causes of BWS. As tumor risk correlates with genetic and epigenetic causes of BWS, several groups have proposed alterations to tumor screening protocols based on the etiology of BWS. However, there are many challenges inherent in adapting screening protocols. Such protocols must accommodate not only the risk based on genetic and epigenetic causes but also the medical cost-benefit of screening, the psychological impact on families, and the social-legal implications of missing a treatable tumor.